MANJISTHA (RUBIA CORDIFOLIA) NATURAL DYE EXTRACTION METHODS FOR SUSTAINABLE TEXTILE APPLICATIONS - N. NIVYA (The Journal of Research ANGRAU, 2026)
The study conducted in 2024 provides acomparative evaluation of four extraction techniques Traditional Fermentation Extraction (TFE), Enzyme Assisted Extraction (EAE), Microwave Assisted Extraction (MAE) and Enzyme Assisted Microwave Extraction (EAME) for efficient recovery of natural dyes from Manjistha (Rubia cordifolia) roots. The objective was to enhance colour strength, dye yield and environmental sustainability in cotton dyeing. Cotton fabrics were dyed with extracts from each method, using both guava leaf powder (bio-mordant) and alum (chemical mordant), with process optimization for pH (optimal at 9), temperature (90°C), dyeing time (60 minutes) and a material-to-liquor ratio of 1:10. Among the methods, EAME achieved the highest dye yield (28.4%) and colour strength (K/S value: 12.3 with alum, 10.9 with guava leaf powder), surpassing traditional fermentation (yield: 12.1%, K/S: 6.2 with alum), EAE (yield: 21.7%, K/S: 9.3 with alum), and MAE (yield: 23.6%, K/S: 10.2 with alum). Additionally, EAME reduced extraction time by 60 percent compared to TFE, demonstrating sustainability advantages. Recycling of dye sludge for re-dyeing achieved up to 68 percent colour strength retention, highlighting an innovative strategy for waste minimization and circular resource use. The synergistic effect of enzyme and microwave treatments not only maximized dye recovery and colour fastness but also reduced environmental impact, positioning EAME as a green and scalable method for natural dye extraction.